THE EFFECT OF CARGO MANAGEMENT, FACILITY MANAGEMENT, AND INFORMATION MANAGEMENT MODERATED BY SECURITY CULTURE ON SUPPLY CHAIN SECURITY OPERATIONAL PERFORMANCE ON THE DELIVERY OF DORE BULLION BY GOLD MINING COMPANIES IN INDONESIA - Rumlaklak, Marchel P; Marie, Iveline Anne (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Gold mining companies in Indonesia must refine gold from dori bullion in Jakarta, which faces various risks, including theft. This study examined the effect of cargo management, facility management, and information management on supply change security operational performance moderated by security culture in gold mining companies in Indonesia. The type of research used is causality research, which is a hypothesis to test the effect of a variable on another variable. The variables used consist of 3 independent variables: cargo management, facility management, and information management; 1 moderating variable, security culture; and 1 dependent variable, supply change security operational performance. The sample withdrawal method uses purposive sampling, namely respondents who work in gold mining companies related to the supply chain for sending Dori bullion. The sample used was 160 respondents, and the analysis tool was SEM-PLS. The findings show that cargo management, facility management, and information management are proven to have a positive effect on supply change security operational performance, while security culture is not proven to moderate the influence of cargo management, facility management, and information management on supply change security operational performance. Keyword : cargo management, facility management, information management, security culture, supply change security operational performance